GIS-based assessment of spatial and temporal disparities of urban health index in Shenzhen, China - Yongheng, Duan; Shan, Xie; Fei, Liu; Jinglin, Tang; Liyue, Gong; Xiaoying, Liu; Tingxiao, Wen; Hongrui, Wang (Frontiers in Public Health, 2024)
Purpose To explore the inter-regional health index at the city level to contribute to the reduction of health inequalities. Methods Employed the health determinant model to select indicators for the urban health index of Shenzhen City. Utilized principal component analysis, the weights of these indicators are determined to construct the said health index. Subsequently, the global Moran’s index and local Moran’s index are utilized to investigate the geographical spatial distribution of the urban health index across various administrative districts within Shenzhen. Results The level of urban health index in Shenzhen exhibits spatial clustering and demonstrates a positive spatial correlation (2017, Moran’s I = 0.237; 2019, Moran’s I = 0.226; 2021, Moran’s I = 0.217). However, it is noted that this clustering displays a relatively low probability (90% confidence interval). Over the period from 2017 to 2019, this spatial clustering gradually diminishes, suggesting a narrowing of health inequality within economically developed urban areas. Conclusion Our study reveals the urban health index in a relatively high-income (Shenzhen) in a developing country. Certain spatially correlated areas in Shenzhen present opportunities for the government to address health disparities through regional connectivity.